2019
DOI: 10.4236/oalib.1105729
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Aspects and Management of Children in Otorhinolaryngological Consultation: Case of University Clinics of Lubumbashi (DR Congo)

Abstract: Introduction: Otorhinolaryngological pathologies in children are a problem in sub-Saharan Africa because they are frequent and complex, yet poorly described, and their management poses a real challenge. The objective of this study was to describe the clinical and therapeutic characteristics, as well as to establish a diagnostic and topographic grouping of the main ENT diseases in children attending the ENT department of the University Clinics of Lubumbashi (DR Congo). Methods: A cross-sectional and retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…In our study, the majority of the consultations (66.5%) were requested for the children in the early and middle childhood. Our result is in agreement with Sandra et al (6), who reported that 53.4% of 309 pediatric consultations were requested for the children between the 3 and 12 years of age.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In our study, the majority of the consultations (66.5%) were requested for the children in the early and middle childhood. Our result is in agreement with Sandra et al (6), who reported that 53.4% of 309 pediatric consultations were requested for the children between the 3 and 12 years of age.…”
Section: Discussionsupporting
confidence: 94%
“…The majority (71.4%) of the consulted children were outpatients in our study. In contrast, Sandra et al (6) reported that only 1.94% of their pediatric consultation cases were referred. In fact, outpatient consultations have been increasing in our hospital in the recent years, probably due to medicolegal considerations.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations